The Ethnic and Linguistic Self-Identification of Ukrainian Speaking Inhabitants of Podlasie. Based on Linguistic Research - Jekaterynczuk, Andrzej (Konteksty Społeczne, 2020)
The aim of the article is to analyze the ethnic and linguistic identification of the Ukrainian-speaking population in the south-eastern part of the Podlaskie Voivodeship. This region is inhabited by the population of the Orthodox denomination, for whom the language spoken at home is Ukrainian (dialect). The article describes the ethnic and linguistic self-identifications of the older generation of the Podlasie residents. The author is interested in how the Ukrainian-speaking residents identify "their own" and "strangers", how they are identified by "strangers": the Polish-speaking majority and Belarusian-speaking minority, and how they themselves identify these groups of "strangers" and whether these identifications coincide. The material basis for the analyses is dialectological research carried out in Podlasie region. Celem artykułu jest analiza identyfikacji etnicznej i językowej ukraińskojęzycznej ludności w południowo-wschodniej części województwa podlaskiego. Region ten zwarcie zamieszkuje ludność wyznania prawosławnego, dla której językiem kontaktów domowych jest język ukraiński (dialekt). W prezentowanym artykule opisano etniczne i językowe autoidentyfikacje starszego pokolenia mieszkańców Podlasia. Autora interesuje jak ukraińskojęzyczni mieszkańcy identyfikują „swoich” i „obcych”, jak sami są identyfikowani przez „obcych”: przez polskojęzyczną większość i białoruskojęzyczną mniejszość, jak sami identyfikują grupy „innych” oraz czy te identyfikacje są ze sobą zbieżne. Bazę materiałową analiz stanowią badania dialektologiczne realizowane na Podlasiu.